Cyprus : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that after four years of strong growth, economic activity in Cyprus has tailed off since late 2001, affected by the global economic slowdown. The authorities estimate growth for 2002 to have declined to 2.3 percent, with falling tourist arrivals and weakening consumer and business confidence. Inflation has risen to 2.9 percent year-over-year in December on account of indirect tax increases, but core inflation remains low. The current account deficit is expected to have deteriorated in 2002 to 5.5 percent, on account of lower tourism receipts and temporary factors.